Heuristics for Systems-of-Systems Design - Imamura, Marcio; Ferreira, Francisco; Santos, Rodrigo (Anais Estendidos do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2022)
A System-of-Systems (SoS) is an arrangement of independent systems that work in synergy to fulfill a common mission. SoS can be observed in several domains such as urban mobility, healthcare, and smart cities, to mention a few. A significant concern of SoS professionals refers to the independence of the constituent systems, which have the autonomy to stop contributing or abandon an SoS, making it difficult to guarantee the quality of SoS at design time. There are concerns involving the design of SoS. Managers, developers, and users should comprehend how the SoS will operate, aiming to mitigate potential problems anticipated at design time, and defining the requirements and resources necessary to develop and maintain the SoS before it starts operating. This Master's thesis aims to investigate good practices and recommendations that can be applied to the design of SoS to assure its proper operation. Therefore, we herein adopted the term ``heuristics" to refer to such good practices and recommendations. A systematic mapping study (SMS) was conducted to identify which heuristics have been applied in SoS design. The SMS results were discussed in a focus group to organize the heuristics in a catalog. To facilitate the understanding and implementation, the heuristics in this catalog have been organized into groups. Each heuristic was categorized according to its suitability for use based on the coordination level of the SoS. We developed a tool that incorporates some of the heuristics from the catalog to verify how the heuristics can facilitate the SoS design process. A feasibility study was conducted with practitioners to evaluate the ease of use and the usefulness of the tool. We expect that the heuristics catalog would support professionals to identify critical issues during the SoS design process.